Mythical images in Kristijonas Donelaitis’ The Seasons: birds - Razauskas, Dainius (Literatūra, 2016)
The article deals with the traditional (folkloric, mythological) images of birds in Kristijonas Donelaitis’ The Seasons, mainly in the first part, “Spring Joys”. The article consists of three sections: the first deals with lines 1.107–108 and 142–144 of The Seasons, which refer to the folkloric imitation of nightingales; second — lines 1.111–114 and 127–130 (taking into account 1.80–84 and 98–104), where the nightingale is compared to sparrows, while the singing nightingale is an equivalent to the būrai (Krizas) worshiping God; third — lines 1.155–201, where Donelaitis describes the election of the “bird king”. All of these topics are folkloric, and the latter two have direct links with mythology.